Metagenomics Reveal Correlations Between Microbial Organisms in Soils and the Health of Populus euphratica - Tuo, Yu; Dong, Zhibao; Wang, Xiping; Gao, Beibei; Zhu, Chunming; Tuo, Fei (Frontiers in Microbiology, 2020)
Biological diversity plays important role in the stability of ecosystems. The Mu Us Desert (MUD), located in Northern China, is an aeolian desert. Although it has been governed by a series of ecological restoration programs, the MUD still has limited biological diversity. Populus euphratica (P. euphratica), a xerophytic plant, has great potential to improve the biological diversity of the MUD. However, the survival rate of P. euphratica in the MUD has been very low. The current study tried to explore the mechanism of the high death rate of P. euphratica in the microbiome perspective. The correlation study between soil community composition and soil properties showed that water-filled pore space (WFPS), pH, EC, AP, NO3- and NH4+ possess higher potential to change the bacterial community (18%) than fungal community (9%). Principal coordinate analysis indicated that the composition of both bacteria (Proteobacteria and Bacteroidetes) and fungi (Ascomycota) in the root soil can be increased by P. euphratica. By systematically comparing between the fungal diversity in the root soil around P. euphratica and the pathogenic fungus extract from the pathogenic site of P. euphratica, we found that, the high death rate of P. euphratica was associated with specific pathogenic fungus Alternaria alternate and Didymella glomerata. In addition, the microbiome composition analysis indicated that P. euphratica planting could also influence the portions of bacteria community which also has great potential to lead to future infection. However, as the extraction and separation of bacteria from plants is challenging, the correlation between pathogenic bacteria and the high death rate of P. euphratica were not studied here and could be explored in future work.